1996
DOI: 10.1073/pnas.93.10.5127
|View full text |Cite
|
Sign up to set email alerts
|

The C-proteinase that processes procollagens to fibrillar collagens is identical to the protein previously identified as bone morphogenic protein-1.

Abstract: Bone morphogenic protein-1 (BMP-1) was originally identified as one of several BMPs that induced new bone formation when implanted into ectopic sites in rodents. BMP-1, however, differed from other BMPs in that it its structure was not similar to transforming growth factor 13. Instead, it had a large domain homologous to a metalloendopeptidase isolated from crayfish, an epidermal growthfactor-like domain, and three regions of internal sequence homology referred to as CUB domains. Therefore, BMP-1 was a member … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(138 citation statements)
references
References 31 publications
(32 reference statements)
3
135
0
Order By: Relevance
“…A number of proteins with a role in embryonic development or immune responses have been identified that contain both the EGF-like and the CUB domains. These include Drosophila tolloid (34) and the mammalian tolloid-like proteins BMP1 (procollagen C proteinase) (35) and mTll (36), sea urchin fibropellins (37), the complement proteins C1s and C1r (37,38), and the serum glycoprotein attractin (39,40). Mouse Scube1 had been reported to be expressed prominently in the developing gonad, nervous system, somites, surface ectoderm, and limb buds (14), whereas mouse Scube2 was restricted to the embryonic neuroectoderm in mouse embryos ranging from 7.5 to 12.5 days post-coitum (15).…”
Section: Discussionmentioning
confidence: 99%
“…A number of proteins with a role in embryonic development or immune responses have been identified that contain both the EGF-like and the CUB domains. These include Drosophila tolloid (34) and the mammalian tolloid-like proteins BMP1 (procollagen C proteinase) (35) and mTll (36), sea urchin fibropellins (37), the complement proteins C1s and C1r (37,38), and the serum glycoprotein attractin (39,40). Mouse Scube1 had been reported to be expressed prominently in the developing gonad, nervous system, somites, surface ectoderm, and limb buds (14), whereas mouse Scube2 was restricted to the embryonic neuroectoderm in mouse embryos ranging from 7.5 to 12.5 days post-coitum (15).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that impair the cleavage site of the C pro peptides cause a mild osteogenesis imperfecta with normal or increased z scores (indicating normal or increased bone mineral density) measured by dual energy X ray absorptio metry. Mutations in BMP1 result in more severe forms of osteogenesis imperfecta than cleavage site mutations, as BMP1 broadly affects extra cellular matrix assembly and structure by processing the C propeptides of type I and type III collagen 48,49 , N propeptides of pro α1(V) and pro α1(XI) 50,51 , cleavage of the collagen and elastin crosslinking enzyme pro lysyl oxidase 52 and of small leucine rich proteoglycans, such as prodecorin and probiglycan 53,54 . BMP1 is also respon sible for the activation of multiple cytokines, such as TGFβ1, BMP2 and BMP4 (REF.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Subsequent to the finding that BMP1 provides pCP activity (Kessler et al, 1996;Li et al, 1996), it was shown that each of the mammalian BMP1/TLD-like proteinases has some level of pCP activity; with BMP1 and mTLL2 showing highest and lowest in vitro pCP levels, respectively Scott et al, 1999). In fact, mTLL2 pCP levels are not observable in vitro, unless procollagen substrates and mTLL2 are co-incubated in the presence of a third protein known to enhance the pCP activity of BMP1/TLD-like proteinases and see below).…”
Section: Fibrillar Collagensmentioning
confidence: 99%
“…Rather, it contains a metalloproteinase domain and initially was thought to act in bone morphogenesis via activation of the TGFβ-like BMPs with which it co-purified . In 1996 BMP1 was independently shown by two groups to provide the procollagen C-proteinase (pCP) activity responsible for cleaving the C-propeptides from procollagens I-III (Kessler et al, 1996;Li et al, 1996). Subsequently, BMP1 has become the prototype of a small group of proteinases with conserved domain structure, shown to process a variety of precursors into mature functional proteins with roles in ECM formation.…”
Section: Introductionmentioning
confidence: 99%